2012
DOI: 10.1088/1367-2630/14/7/075010
|View full text |Cite
|
Sign up to set email alerts
|

Carrier–envelope phase-tagged imaging of the controlled electron acceleration from SiO2nanospheres in intense few-cycle laser fields

Abstract: Waveform-controlled light fields offer the possibility of manipulating ultrafast electronic processes on sub-cycle timescales. The optical lightwave control of the collective electron motion in nanostructured materials is key to the design of electronic devices operating at up to petahertz frequencies.We have studied the directional control of the electron emission from 95 nm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…This behavior is expected for the case, where charge interaction effects can either be neglected or contribute a constant enhancement factor to the cutoffs, similar to what has been observed for the photoemission from nanoparticles. 46 Following this argument, we can define a relation between the experimentally observed cutoff and the incident laser intensity as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is expected for the case, where charge interaction effects can either be neglected or contribute a constant enhancement factor to the cutoffs, similar to what has been observed for the photoemission from nanoparticles. 46 Following this argument, we can define a relation between the experimentally observed cutoff and the incident laser intensity as follows:…”
Section: Resultsmentioning
confidence: 99%
“…23,24,46 There, the electron emission leads to the creation of a positive charge localized at the surface, creating a trapping potential from which direct electrons cannot escape due to their low kinetic energy. Consequently, direct electrons are completely suppressed and there is a relatively clear asymmetry also at lower kinetic energies.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments on dielectric SiO 2 nanospheres by Zherebtsov et al [46,47] in strong few-cycle laser fields illustrated the importance of charge interaction with respect to the electron acceleration mechanism. It was found that the highest kinetic energies in the rescattering plateau extend up to T cutoff ≈ 53U p , much higher than the expectation of T cutoff = 23U p , derived from the classical 10U p -cutoff formula and the field enhancement factor alone.…”
Section: Modifications By Collective Excitations/space Chargementioning
confidence: 99%
“…The setup used in experiments on isolated dielectric nanospheres [47] is depicted in Figure 6.8. Single, isolated nanoparticles were injected by an aerodynamic lens system into the laser focal region inside a single-shot velocity-map imaging (VMI) spectrometer, operating at 1 kHz image acquisition rate.…”
Section: Cep-dependent Photoemission From Sio 2 Nanospheresmentioning
confidence: 99%
See 1 more Smart Citation